Application of response surface methodology (RSM) for the optimization of supercritical CO2 extraction of oil from patè olive cake: Yield, content of bioactive molecules and biological effects in vivo. (1st December 2020) - Durante, M.; Ferramosca, A.; Treppiccione, L.; Di Giacomo, M.; Zara, V.; Montefusco, A.; Piro, G.; Mita, G.; Bergamo, P.; Lenucci, M.S.
Highlights: RSM was effective to optimize SC-CO2 oil extraction from patè olive cake (POC). Under the optimized operative conditions, 65% of the total POC oil was extracted. SC-CO2 extracted POC oil had higher concentrations of lipophilic bioactives than EVOO. POC oil oral administration (0–40 µL·die −1 ) had no effects on mice liver redox status. POC oil molecules may be useful to improve/restore mitochondrial defective functions. Abstract: The two-phase technology for olive oil extraction generates large amounts of patè olive cake (POC), a by-product that is rich in bioactive health-promoting compounds. Here, response surface methodology (RSM) was used to maximize supercritical-CO2 oil extraction from POC, while minimizing operative temperature, pressure and time. Under the optimal parameters (40.2 °C, 43.8 MPa and time 30 min), the oil yield was 14.5 g·100 g −1 dw (~65% of the total oil content of the freeze-dried POC matrix), as predicted by RSM. Compared with freeze-dried POC, the oil contained more phytosterols (13-fold), tocopherols (6-fold) and squalene (8-fold) and was a good source of pentacyclic triterpenes. When the biological effects of POC oil intake (20–40 µL·die −1 ) were evaluated in the livers of BALB/c mice, no significant influence on redox homeostasis was observed. Notably, a decline in liver triglycerides alongside increased activities of NAD(P)H:Quinone Oxidoreductase 1, Carnitine Palmitoyl-CoA Transferase and mitochondrial respiratory complexes suggested a potential beneficial effect on liver fatty acid oxidation.